Balancing act: exploring the impact of work–family conflict on anxiety among working parents with family health as a mediator - Chaochan Su; Meng Yang; Qiuxia Huang; Min Yang (Frontiers in Psychology)
ObjectiveThe increasing prevalence of work–family conflict and anxiety among working parents, particularly in China, underscores the importance of understanding their interrelationship. This study sought to investigate the relationship between work–family conflict (WFC) and anxiety among working parents while exploring the mediating role of family health in this relationship.MethodsA large-scale cross-sectional survey was conducted using data from the 2021 Psychology and Behavior Investigation of Chinese Residents. The sample comprised 5,068 occupational parents who met the research criteria. Anxiety was assessed using the 7-item Generalized Anxiety Disorder scale, WFC was measured using the WFC scale, and family health was evaluated using the Short Form of the Family Health Scale. Multinomial logistic regression and mediation analyses were applied to examine relationships.ResultsAmong the participants, 58.4% reported no symptoms of anxiety, 30.6% experienced mild anxiety, and 11.0% reported moderate to severe anxiety. Scores for WFC and family health demonstrated significant associations with anxiety levels. Specifically, higher levels of WFC were associated with an increased risk of mild anxiety (odds ratio [OR] = 1.058, 95% confidence interval [CI]: 1.051–1.064) and moderate to severe anxiety (OR = 1.123, 95% CI: 1.111–1.135). Conversely, higher family health scores were associated with a decreased risk of mild anxiety (OR = 0.934, 95% CI: 0.924–0.945) and moderate to severe anxiety (OR = 0.859, 95% CI: 0.842–0.876). Mediation analysis revealed that family health significantly mediated the relationship between WFC and anxiety levels (p < 0.05).ConclusionThe findings confirm a significant relationship between WFC and anxiety, with family health serving as a partial mediator. These results suggest that improving family health may represent an effective strategy for reducing anxiety among working parents.